Distribución geográfica del género Anastrepha en la provincia de Cotopaxi. - Basantes Quinatoa, Miguel Ángel (2021)
The research was carried out from 2014 to 2020. The general objective was to know the geographical distribution of the species of fruit flies of the genus Anastrepha in Cotopaxi Province. To identify, it was evaluated in hosts and species captured in McPhaill traps. To monitor, McPhaill traps were used, which serves as a food attractant; the hydrolyzed protein was used, prepared based on the following proportions of ingredients for 1 lt of mixture: Hydrolyzed Protein 50 to 100 cc (5 to 10%), granules Borax 30 g (3%), and Water 920 to 870 cc. 250 cc .of the mixture is placed in each trap, and the trap is placed on the fruit trees. The collection of data and specimens was carried out every seven days. Once the samples of both specimens and fruits were obtained, the laboratory proceeded as follows: a) The fruits that enter the laboratory (maturation area) were weighed and placed in the hatching chamber, 5 cm of sand and covered with mesh, in a sheltered and ventilated place. b) Once they have hatched or reached their adult stage where flies reach all the optimal characteristics for their identification at the species level. c) To identify and classify the different Anastrepha species, the specific dichotomous keys for the identification of fruit flies by Fernández, Tigrero, Sagacarpa, and Korytkowski were used. Both the fruit flies collected from the traps and those from the hatching chambers were identified at a morphological level, and particular emphasis was placed on the female genitalia, considering necessary to investigate in this field due to the few studies carried out in the country and the importance that has taken over fruit growing for export purposes in Cotopaxi province. In Cotopaxi province, nine species of fruit flies of the genus Anastrepha were identified captured in traps placed on cultivated plants and backyard plants, which are: Anastrepha fraterculus, Anastrepha striata, Anastrepha distincta, Anastrepha leptozona, Anastrepha obliqua, Anastrepha serpentina, Anastrepha atrox, Anastrepha pickeli, and Anastrepha sp. In the fruit trees that are hosts of fruit flies of the Anastrepha genus: "Capulí" (Prunus salicifolia), Peach (Prunus persica), "Guaba" (Inga edulis), Guava (Psidium guajava), Blackberry (Rubus ulmifolius), Orange (Citrus x sinensis), Star apple (Chrysophyllum cainito) and Sour orange (Citrus × aurantium).